Differentiating between different forms of moral obligations. (30th April 2020) - Anderson, Rajen A.; Ruisch, Benjamin C.; Pizarro, David A.
Abstract: We argue that Tomasello's account overlooks important psychological distinctions between how humans judge different types of moral obligations, such as prescriptive obligations (i.e., what one should do) and proscriptive obligations (i.e., what one should not do). Specifically, evaluating these different types of obligations rests on different psychological inputs and has distinct downstream consequences for judgments of moral character.